Positional Candidate Cloning of a QTL in Dairy Cattle: Identification of a Missense Mutation in the Bovine DGAT1 Gene with Major Effect on Milk Yield and Composition - Grisart, Bernard; Coppieters, Wouter; Farnir, Frédéric; Karim, Latifa; Ford, Christine; Berzi, Paulette; Cambisano, Nadine; Mni, Myriam; Reid, Suzanne; Simon, Patricia; Spelman, Richard; Georges, Michel; et al. (Genome Research, 2002)
We recently mapped a quantitative trait locus (QTL) with a major effect on milk composition—particularly fat content—to the centromeric end of bovine chromosome 14. We subsequently exploited linkage disequilibrium to refine the map position of this QTL to a 3-cM chromosome interval bounded by microsatellite markers BULGE13and BULGE09. We herein report the positional candidate cloning of this QTL, involving (1) the construction of a BAC contig spanning the corresponding marker interval, (2) the demonstration that a very strong candidate gene, acylCoA:diacylglycerol acyltransferase (DGAT1), maps to that contig, and (3) the identification of a nonconservative K232A substitution in the DGAT1 gene with a major effect on milk fat content and other milk characteristics.[The sequence data described in this paper have been submitted to the GenBank data library under accession number AY065621.]
10.1101/gr.224202